2021
DOI: 10.5415/apallergy.2021.11.e41
|View full text |Cite
|
Sign up to set email alerts
|

Identification of predictors for persistence of immediate-type egg allergy in Chinese children

Abstract: Background Egg allergy is one of the most common food allergies in childhood with increasing prevalence in Hong Kong. While ample studies were published on its optimal diagnosis, there was limited data on predictors for the natural history of egg allergy in Asian populations. Objective This study aimed to characterize the clinical course and outcome of children with egg allergy and identify its prognostic factors. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
2
4
0
Order By: Relevance
“…The natural history for egg and milk allergies suggested that most patients outgrew 25,26 and, as in the United States, patients have more shellfish exposure in adulthood 27 . Since Hong Kong is a westernized city, we believed the same situation is happening here 4,28–30 . This finding is comparable to recent research on pediatric anaphylaxis patterns, that food triggers such as milk and eggs are predominantly seen in the age group from birth to 4 years, while shellfish is the highest allergen trigger, usually at a later age factor 6 …”
Section: Discussionsupporting
confidence: 87%
“…The natural history for egg and milk allergies suggested that most patients outgrew 25,26 and, as in the United States, patients have more shellfish exposure in adulthood 27 . Since Hong Kong is a westernized city, we believed the same situation is happening here 4,28–30 . This finding is comparable to recent research on pediatric anaphylaxis patterns, that food triggers such as milk and eggs are predominantly seen in the age group from birth to 4 years, while shellfish is the highest allergen trigger, usually at a later age factor 6 …”
Section: Discussionsupporting
confidence: 87%
“…Ngai et al (6) reported egg allergy resolved at 71% of Chinese children with a median of 36 months. Boyana-Martinez et al (7) followed 58 patients prospectively until egg tolerance developed.…”
Section: Discussionmentioning
confidence: 99%
“…Arikyilmaz et al (10) reported that initial egg sIgE level 6.2kU/L could distinguish tolerance or persistence at the age of 6. Another study also found baseline sIgE level and initial symptoms to be independent predictors for resolution (6). Schrier et al( 5) also published elevated egg sIgE levels were related to persistent egg allergy.…”
Section: F O R P U B L I C a T I O Nmentioning
confidence: 91%
See 1 more Smart Citation
“…This allergy can cause serious skin reactions, nasal congestion, and gastrointestinal and respiratory symptoms [ 21 ]. Egg allergies may also coexist with other food allergies, such as nuts and fish [ 22 , 23 ]. A diet exempt of egg is the only solution to manage an egg allergy [ 24 ].…”
Section: Introductionmentioning
confidence: 99%